Analysis of Reading Difficulties for SDN 03 Bilah Barat Students New Linggahara Cliff Village - Muhammad Husni Ritonga; Jainuar Amarullah Lubis (Edumaspul: Jurnal Pendidikan, 2023)
The issue discussed in this study is the problem of low reading ability in students. Therefore, an in-depth analysis of the obstacles that affect the students' reading ability is needed. The aim of this research is to determine the elements that hinder students' reading abilities. The method used in this research is a descriptive approach within a qualitative research framework. Several students from SDN 03 Bilah Barat were the focus of this research. Data was collected in two ways, namely through direct observation (observation) and face-to-face conversation (interview). The results of this research indicate that students' lack of interest and motivation to develop reading skills is the main cause of students' reading difficulties. Besides that, Lack of learning support and attention from parents or family also influences efforts to overcome children's reading difficulties. Educators have taken steps to overcome problems in students' reading learning. This includes providing students with regular assignments, facilitating access to books through loans, providing praise and encouragement to increase enthusiasm for learning, and organizing extra sessions or tutoring for students who face reading difficulties.